Type 2 Diabetes Mellitus Among Youth in Puerto Rico, 2003 - Pérez-Perdomo, Rosa; Pérez-Cardona, Cynthia M.; Allende-Vigo, Myriam; Rivera-Rodríguez, Mariam I.; Rodríguez-Lugo, Luis A. (Puerto Rico Health Sciences Journal, 2005)
see manuscript